Položaj, upravljanje in financiranje javnih agencij v Republiki Sloveniji - Bohinc, Rado (Podjetje in delo, 2024)
In this paper, we first discuss the founding of a public agency and related open questions, especially the importance of the founding act, the name of the public agency, the regulation of management and assets, and the financing of the public agency in the very diverse practice that followed the adoption of the Public Agencies Act. There are large differences in the regulation of these issues in the sectoral legislation due to the rule that the Public Agencies Act applies only to the extent that the sectoral legislation does not provide otherwise. In the two decades since the enactment of the law, this has led to the diversity of the regulation of fundamental issues to such an extent that today it is difficult to talk about one type of a public agency in the Republic of Slovenia. For some public agencies, the Public Agency Act does not apply in its entirety, with only some of the expressly listed provisions applying. The term agency is also used for other entities under public law (funds, limited liability companies, public economic institutions) and even government departments or constituent body within ministries. The founding act does not include all the tasks of an individual public agency. The role of the founder in the management of the public agency is decisive, which has a significant impact on the implementation of the legal rule on the independence of the public agency. According to the Public Agency Act, the founder appoints and dismisses the director and also the members of the public agency council. Despite these provisions of the Public Agency Act, individual sectoral laws have introduced numerous exceptions for the operation of the councils. Differences from the provisions of the Public Agencies Act are in the method of appointing the director, the length of their mandate, and the composition of the public agency council. It has been observed that only half of the public agency founding acts explicitly specify who should sign the director's employment contract. Among the most important differences is the fact that the directors of public agencies are also chairmen of public agency councils, and in some cases other employees could be public agency council members despite this being prohibited. The content of the employment contracts for the director of individual public agencies is not legally uniform. The Public Agencies Act prohibits the founder from investing premises and equipment in a public agency as a newly established legal entity. It is difficult to rationally explain why such a provision is in the law. A public agency is established, among other things, as stated in the Public Agencies Act (Article 4), if this enables a more effective and efficient performance of tasks, especially if the performance of administrative tasks can be fully or mainly financed by administrative fees or user payments. According to the Public Agencies Act, administrative fees are considered the revenue of the budget, and not the revenue of the public agency (Article 42), which is a questionable arrangement from the point of view of the legally set criterion in Article 4 of the Public Agencies Act, specifically that the public agency is fully or mainly financed by administrative fees or user payments. Regardless of the provision of Article 39 of the Public Agencies Act, that the premises and equipment remain the property of the founder, i.e. that the public agency cannot own the premises, the public agency can have its own other assets, with which, as stipulated by the Public Agencies act, it guarantees for the obligations of the public agency.